2022
DOI: 10.1186/s12877-022-02995-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between new health conditions and healthcare service utilizations among older adults in the United Kingdom: effects of COVID-19 risks, worse financial situation, and lowered income

Abstract: Background Health services are critically important for older adults, particularly during the Coronavirus disease-19 (COVID-19) pandemic. However, COVID-19 risks, worse financial situation, and lowered income may seriously impact health services by feasibility and accessibility. Therefore, the aim of the present study was empirically to explore how health-seeking behaviors are influenced by new health conditions through COVID-19 risks, worse financial situation, and lowered income. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Accessibility to healthcare services may have been restricted in the absence of health insurance. Several studies have documented nancial barriers to access to health services [30] which is not the case in this study as 85% of the respondents had health insurance coverage. The high percentage of insurance coverage among the study respondents is attributed to the mandatory health insurance scheme offered for all nationals and expatriates in the UAE [31,32].…”
Section: Discussionmentioning
confidence: 73%
“…Accessibility to healthcare services may have been restricted in the absence of health insurance. Several studies have documented nancial barriers to access to health services [30] which is not the case in this study as 85% of the respondents had health insurance coverage. The high percentage of insurance coverage among the study respondents is attributed to the mandatory health insurance scheme offered for all nationals and expatriates in the UAE [31,32].…”
Section: Discussionmentioning
confidence: 73%
“…Education and income are as well-known determinants of health and healthcare utilization, and we found that they were associated with interruptions in accessing needed healthcare. Prior to the COVID-19 pandemic, it was widely recognized that financial hardship limited the accessibility of needed health services, and income continued to connect pandemic-induced barriers with both delayed and foregone health care [ 39 , 40 ]. Those with lower income experienced greater difficulties in meeting their healthcare needs, further exacerbating existing inequalities in healthcare, particularly among men.…”
Section: Discussionmentioning
confidence: 99%